CHALLENGES OF DEVELOPMENT OF THEORETICAL BASES IN INTERCULTURAL COMMUNICATION AS THE FIRST FACTOR OF TEACHING FOREIGN ANGUAGES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, the main problems of the theoretical bases of development of intercultural communication as an important factor in teaching a foreign languages are revealed. The author highlights the key tendencies and problems in this sphere.